A STUDY ON CUSTOMER'S PERCEPTION OF POST-PANDEMIC PRICING STRATEGY OF BANKS - Reeta Pant; Dr. H.R. Kaushal, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The COVID-19 pandemic has spurred changes in service delivery practices around the world. It is commonly acknowledged that COVID-19 will continue to cause uncertainty for the foreseeable future. Massive modifications in banks marketing strategies were made during the pandemic period to meet unexpected conditions. Customers expect their banks to provide higher quality services at a reasonable price, which if met, might lead to increased customer satisfaction and retention. As the pandemic progresses, banks and other non-financial companies around the world are left with no choice but to reconsider their future marketing tactics, as traditional marketing methods have been hampered by the lockdown. Due to the lockdown for a long period, many people lost their livelihoods for some time or permanently. Some have already suffered salary cutbacks and practically everyone’s assessments are being delayed - employees are apprehensive and concerned about their future as a result of the pandemic issue and lockdown. This study aims to identify what the customers are now expecting from their bank regarding interest charged or paid or any penalty or other price paid or charged by the bank which will directly influence them. Such analysis shall help to suggest an appropriate pricing policy to form according to customers’ expectations.